Coherent population of magnetic sublevels of 2p3/2 state in hydrogenlike uranium by radiative recombination - Tashenov, Stanislav; Jörg, Holger Eric; Litvinov, Yuri A. (Physica scripta, 2015)
The x-rays emitted in the process of radiative recombination (RR) of quasi-free electrons into excited state of hydrogenlike uranium ion were studied experimentally. Both the RR x-ray and the subsequently emitted x-ray were detected in time-coincidences. The angular distribution of the x-rays varied as a function of the RR x-ray emission direction. This observation revealed the coherent population of magnetic sublevels of the state in the hydrogenlike uranium ion.
Im Text ist 3/2 tief gestellt
Gesehen am 29.06.2020